Review methods for clock skew measurement - Azmir, Azra Ariel; Wirastuti, Ni Made Ary Esta Dewi; Saputra, Komang Oka (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Clock skew is the deviation of the clock from the true time, which makes it an important role in time information. Clock skew is unavoidable and causes each clock to run at a different speed, so there is a very slight difference between them, but it can still be observed properly. The known properties of clock skew make it potential research for many experts, such as Paxson, Aoki, and Huang. To produce a more accurate clock skew measurement, this study uses the ant colony optimization method by adopting the behavior of an ant colony in searching for food by choosing the path with the shortest route, which will become the cluster offset as a material for measuring clock skew. Ant colony optimization method has the most potential to be adapted in clock skew measurement because the cluster offset is not affected by the upper and the bottom outliers to produce an accurate clock skew measurement.